(3HZjI GdQGZH aj TQM eQTOI GdWGdH dGHf GdgGFes - (3YHO Gddg Hf eMeO GdTfThQi GdaQVi GdTGaYjs; (3GHf GdgGFe , TgGH GdOjf CHh GdYHGS GdefUhQj,J (B887 (3g` s ((3SdjeGf GdhGWi GdeGdci s)
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg, hGdUdGI hGdSdGe Ydi SjOfG eMeO s
(3BNQgG (B:s
(3hCSCd Gddg GdYXje Cf jLYdg NGdUkG dhLgg GdcQje s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B220s
Keywords: (3GdQjGVjGJs